2013
DOI: 10.3989/egeol.40781.168
|View full text |Cite
|
Sign up to set email alerts
|

Mise en évidence d’un Sénonien gypseux sous la série phosphatée du bassin des Ouled Abdoun: Un nouveau point de départ pour l’origine des zones dérangées dans les mines à ciel ouvert de Khouribga, Maroc

Abstract: In the Ouled Abdoun sedimentary basin (Morocco), the phosphatic series is composed of regular interbedded phosphatic and marly limestone layers. Exploitation of the phosphate in some deposits in this basin collides frequently with problems bound to the existence, in the phosphatic series, of disturbed areas (sterile bodies) qualified as derangements by the mining engineers of the Office Cherifian Phosphate Group (OCP). Their presence in the phosphatic layers causes two kinds of problems: (1) since the whole ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The Ouled Abdoun Basin is one of the ancient epicontinental marine basins along the Atlantic coast of Africa, where large amounts of phosphorite accumulated during the late Cretaceous -early Eocene period. The basement rocks are covered by Cenomanian-Turonian carbonates followed by yellow marls with possible age within the Coniacian-Campanian interval (El Assel et al, 2013), which were eventually succeeded by the phosphorite series.…”
Section: Geological and Stratigraphical Settingsmentioning
confidence: 99%
“…The Ouled Abdoun Basin is one of the ancient epicontinental marine basins along the Atlantic coast of Africa, where large amounts of phosphorite accumulated during the late Cretaceous -early Eocene period. The basement rocks are covered by Cenomanian-Turonian carbonates followed by yellow marls with possible age within the Coniacian-Campanian interval (El Assel et al, 2013), which were eventually succeeded by the phosphorite series.…”
Section: Geological and Stratigraphical Settingsmentioning
confidence: 99%
“…Beneath the 70 m depth, the top of moderately resistant layers is locally observed. They correspond to the compact gray marl with gypsum of the Senonian, which can be seen in the OCP's recognition wells at this depth [43]. Above the conductive horizon, moderately resistant and resistant soils consisting of phosphatic layers with very low water content with intercalated limestone and flint layers occur.…”
Section: Khouribga Mining Sitementioning
confidence: 79%
“…Other resistant bodies also cut the phosphatic series. They are attributed to the disturbed areas of the phosphatic series, known as "derangements" by the OCP mining engineers [43][44][45][46]. These structures are often accompanied by a localized silicification event.…”
Section: Khouribga Mining Sitementioning
confidence: 99%
“…These bodies are characterized by an irregular geometrical shape and dispersed without any order or privileged direction under a Quaternary cover. The geological investigations carried out in Sidi Chennane deposit have revealed that the origin of these structures is linked to the dissolution of the Senonian gypsiferous layers situated at the base of the phosphate series [3]. Their detection and delimitation required in many cases several exploration works, such as drilling wells that remain not particularly effective and increase drastically the cost of phosphate extraction.…”
Section: Introductionmentioning
confidence: 99%